New players in phototherapy: photopharmacology and bio-integrated optoelectronics. (June 2019) - Morstein, Johannes; Trauner, Dirk
Abstract : Photodynamic therapy and phototherapy are used in the clinic to treat dermatological conditions, cancer, macular degeneration, and a variety of other diseases. Despite their long history and widespread application, the scope of these therapeutic approaches has been limited by a lack of specificity and challenges with light delivery. In recent years, much progress has been made in these regards. Photopharmacology has provided drug-like molecules that change their efficacy upon irradiation and allow for the optical control of a wide range of defined biological targets. Many photopharmaceuticals are now used in vivo and some show promising results in preclinical development. At the same time, new bioelectronics for subdermal light delivery have been engineered that could enable phototherapy deep in tissue, for example within the human brain. These developments could increase the impact of photodynamic therapy in human precision medicine.